Enhanced expression of endogenous retroviruses and of TRIM28 and SETDB1 in children with food allergy - Tovo, Pier‐Angelo; Monti, Giovanna; Daprà, Valentina; Montanari, Paola; Calvi, Cristina; Alliaudi, Carla; Sardo, Allegra; Galliano, Ilaria; Bergallo, Massimiliano (Clinical and translational allergy, 2022)
Background Human endogenous retroviruses (HERVs) represent 8% of our genome. They originate from ancestral infections and although no longer contagious they can regulate transcription of adjacent cellular genes, produce viral RNAs sensed as non‐self by pattern recognition receptors, and encode viral proteins, such as Syncytin (SYN) 1 and 2, that exhibit potent immunomodulatory properties. Based on this, HERVs have been studied and proposed as relevant cofactors in several chronic inflammatory and immune‐mediated diseases. HERV transcription is regulated by host TRIM28 and SET domain bifurcated histone lysine methyltransferase 1 (SETDB1), which in turn exert crucial regulatory functions on the host immune system. No studies explored the expression of HERVs, TRIM28, and SETDB1 in allergic patients. Methods We assessed, through a polymerase chain reaction real time Taqman amplification assay, the transcription levels of pol genes of HERV‐H, HERV‐K, HERV‐W, and of env genes of SYN1 and SYN2, as well as of TRIM28 and SETDB1 in whole blood from 32 children with IgE‐mediated food allergy, 19 with food protein‐induced enterocolitis syndrome (FPIES), and in healthy control children. Results The expression levels of pol genes of HERV‐H, ‐K, and ‐W were significantly enhanced in patients with IgE‐mediated FA or FPIES as compared to control subjects, while the mRNA concentrations of SYN1 and SYN2 were comparable in each group of children. Both TRIM28 and SETDB1 mRNA levels were significantly higher in allergic patients. Conclusions Given the influence of HERVs and of TRIM28 and SETDB1 on innate and adaptive immune responses, their transcriptional activation in children with food allergies suggest that they might play important roles in the development of these diseases.